Efficacy of Omaha system-based nursing management on nutritional status in patients undergoing peritoneal dialysis: A randomized controlled trial protocol. Issue 51 (18th December 2020) - Peng, Liqing; Gao, Yuanyuan; Lu, Rong; Zhou, Ruixiang
Abstract : Abstract: The chronic kidney disease (CKD) patients may have a variety of complications during receiving peritoneal dialysis (PD). The malnutrition in CKD patients is related to their lower life quality, higher hospitalization rates, and higher risk of cardiovascular disease, as well as the increased morbidity and mortality. Hence, it is very important to monitor and then manage the nutritional status of CKD patients. Thus, we perform this randomized controlled study protocol to introduce a continuing nursing program based on Omaha system (OS) for the patients with CKD receiving PD treatment. The randomized trial will be implemented from November 2020 to May 2021 and was granted through the Research Ethics Committee of Wuhan No.1 Hospital (2020003281). Two hundred patients meet inclusion criteria and exclusion criteria are included. Patients who meet the following criteria will be selected: voluntary participation, aged 20 to 60; undergoing the regular PD treatment for at least 3 months. Patients will be excluded if the patients are in unstable status, or experience the intermittent PD or some other kinds of dialysis mode, have severe cachexia, infection, or malnutrition, or if they have mental disorders. In control group, patients are given routine treatment, containing general guidance associated with PD and the outpatient telephone calls from the clinical nurses during follow-up. In study group, the patients are given the continuous nursing treatment scheme based on OS. The clinical results are the biochemical parameters after intervention, anthropometry, as well as the subjective global assessment. Table 1 reveals the clinical endpoints between the 2 groups. This protocol can guide nurses to develop a nursing program based on evidence for patients with CKD receiving PD. Trial registration: This study protocol was registered in Research Registry (researchregistry6202).